An Empirical Method of Comparing Brisance of Various Bulk Explosives - Neal Lee; Braden T. Lusk; Brendan McCray (International Society of Explosives Engineers, 2017)
"Selection of a blasting agent for optimum performance is based on many variables. Often, a decision is made with regard to product cost and field testing. Defining optimum performance can be difficult, since downstream effects of fragmentation on loading, haulage, processing, and energy consumption are not immediately clear. Many operations are beginning to optimize their blasting programs “on the bench,” by utilizing information generated downstream at the loader and/or crusher. During the evaluation of a blasting agent, factors such as velocity of detonation, gas production, and sensitivity are typicallyconsidered. Alternatively, brisance (“the shattering power of an explosive material distinguished from its total work capacity”1) is not. Brisance affects the immediate area surrounding a borehole. Fractures produced here during the shock phase of detonation are believed to have an important effect on rock movement and fragmentation. "